Inklusifitas Informasi Pengguna Difabel Studi Kasus Dinas Perpustakaan dan Arsip Provinsi Sumatera Utara: Inclusiveness of Information for Users with Disabilities Case Study of the Library and Archives Service of North Sumatra Province - Annisa fitri; Franindya Purwaningtyas (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to analyze the inclusiveness of information for users with disabilities at the Library and Archives Service of North Sumatra Province. The main focus of this study is to identify obstacles, facilities, and efforts made by the Library and Archives Service of North Sumatra Province in providing access to information that can be accessed by people with disabilities. This study uses a qualitative approach with a case study method conducted at the Library and Archives Service of North Sumatra Province. Data collection techniques were carried out through in-depth interviews with library officers, direct observation of existing facilities and services, and documentation studies. The results of the study indicate that although several inclusive steps have been taken, such as the provision of braille books and physical accessibility, there are still obstacles in terms of the use of more disability-friendly technology and the lack of training for library officers related to services for people with disabilities. Therefore, this study recommends improving technological infrastructure, increasing training for library staff, and developing more comprehensive policies to support the inclusiveness of information for all users, especially people with disabilities. This study is expected to contribute to the development of inclusive policies and practices in the field of libraries and archives, as well as raising awareness of the importance of equal access to information for all groups. This study concludes that to achieve better information inclusivity, there needs to be an increase in the provision of disability-friendly facilities, training for officers, and increased use of technology that supports information accessibility for users with disabilities.